Successful management of uncommon complication after brachiocephalic vein catheterization: A case report - Namita Mishra; Danish Qutub; Umesh Bhadani (Journal of Pediatric Critical Care)
Central venous catheterization is an inextricable requirement in intensive care units, long surgeries, postoperative care, and as a part of malignancy treatment that delivers intravenous fluids, drugs, inotropic agents, and intravenous feeding. Recently, different approaches for brachiocephalic vein cannulation gained interest in children and adults. We aimed to describe the rare complication of pleural effusion occurred after brachiocephalic catheterization and managed the case related to cannulation. We tried to emphasize that great vigilance is required at the time of transferring the patient to prevent the displacement and dislodgement of catheter.